2023
DOI: 10.3390/toxics11060503
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone H3K18 Acetylation-Dependent Antioxidant Pathways Involved in Arsenic-Induced Liver Injury in Rats and the Protective Effect of Rosa roxburghii Tratt Juice

Abstract: Arsenic is a common environmental toxicant. Long-term arsenic exposure can induce various types of liver injury, but the underlying mechanism remains unclear, so effective prevention and treatment measures are unknown. This study aims to explore the mechanism of arsenic-induced rat liver injury based on the histone H3K18 acetylation-dependent antioxidant pathway and to identify the role of a medicinal and edible resource, Rosa roxburghii Tratt juice, in combating it. Hepatic steatosis and inflammatory cell inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Previously, we identified the suppression of H3K18ac as an epigenetic marker in response to arsenic exposure and associated with increased risk of arsenic poisoning (the main manifestations of skin and liver damage) using a population study [23]. In an animal model of sub-chronic arsenic exposure, we demonstrated that H3K18ac might be involved in arsenic-induced early liver damage by modulating oxidative damage [24]. This study further uncovered the important role of H3K18ac-dependent LSEC dedifferentiation in arsenic-induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously, we identified the suppression of H3K18ac as an epigenetic marker in response to arsenic exposure and associated with increased risk of arsenic poisoning (the main manifestations of skin and liver damage) using a population study [23]. In an animal model of sub-chronic arsenic exposure, we demonstrated that H3K18ac might be involved in arsenic-induced early liver damage by modulating oxidative damage [24]. This study further uncovered the important role of H3K18ac-dependent LSEC dedifferentiation in arsenic-induced liver fibrosis.…”
Section: Discussionmentioning
confidence: 93%
“…We previously identified a specific site of histone modification in response to arsenic exposure, histone H3 lysine 18 acetylation (H3K18ac), and demonstrated its involvement in arsenic-induced oxidative damage and liver injury [23,24]. This suggests that H3K18ac may be a key driver of arsenic-triggered adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%